Placement of Covered Stents for Carotid Blowout in Patients with Head and Neck Cancer: Follow-up Results after Rescue Treatments - Pyun, H.W. (AJNR Am J Neuroradiol, 2007)
BACKGROUND AND PURPOSE: Placement of a covered stent to control carotid blowout (CB) in malignant tumors of the head and neck has been reported to be an effective treatment. However, it is not uncommon to encounter recurrent hemorrhage. The purpose of this study was to evaluate the follow-up results of patients treated with covered stents. MATERIALS AND METHODS: We retrospectively reviewed the results of 7 consecutive patients who underwent placement of a covered stent to control CB. Most of them had poor wound healing because of previous irradiation, surgery, or both. The initial procedures were successful in all patients. Their clinical course was reviewed for rebleeding, additional endovascular treatments in recurrent cases, and outcomes. RESULTS: Recurrence developed in 6 of 7 patients. The interval between the first procedure and the hemorrhagic event was from 3 to 44 days. In 6 patients who had a recurrent CB, 4 had rebleeding from the previous site of the stent, whereas 2 other patients experienced recurrent bleeding in a different area from the site of the stent. Additional endovascular treatments were carried out in all affected patients by another insertion of a covered stent (n = 3), coil embolization (n = 2), or insertion of a covered stent followed by permanent arterial occlusion (n = 1). CONCLUSION: Placement of a covered stent in patients with head and neck cancer who sustain CB showed frequent rebleeding despite favorable initial rescue results. Recurrent CB at the previous stent site developed frequently in patients with uncontrolled wound infection. Concomitant or short-interval arterial trapping should be considered selectively in those conditions.